A functional unbalance of TRPM8 and Kv1 channels underlies orofacial cold allodynia induced by peripheral nerve damage - Piña, Ricardo; Ugarte, Gonzalo; Guevara, Camilo; Pino, Richard; Valdebenito, Katherine; Romero, Sofía; Gómez del Campo, Ana; Cornejo, Víctor Hugo; Pertusa, María; Madrid, Rodolfo (Frontiers in Pharmacology, 2024)
Cold allodynia is a debilitating symptom of orofacial neuropathic pain resulting from trigeminal nerve damage. The molecular and neural bases of this sensory alteration are still poorly understood. Here, using chronic constriction injury (CCI) of the infraorbital nerve (IoN) (IoN-CCI) in mice, combined with behavioral analysis, Ca 2+ imaging and patch-clamp recordings of retrogradely labeled IoN neurons in culture, immunohistochemistry, and adeno-associated viral (AAV) vector-based delivery in vivo, we explored the mechanisms underlying the altered orofacial cold sensitivity resulting from axonal damage in this trigeminal branch. We found that cold allodynia induced by IoN-CCI is linked to an increase in the proportion of cold-sensitive neurons (CSNs) contributing to this branch and a shift in their thermal thresholds to higher temperatures. These changes are correlated to a reduction of the Kv1.1-1.2-dependent brake potassium current IKD in IoN CSNs and a rise in the percentage of trigeminal neurons expressing TRPM8. The analysis of the electrophysiological properties of CSNs contributing to the IoN suggests that painful cold hypersensitivity involves the recruitment of silent nociceptive afferents that become sensitive to mild cold in response to nerve damage. Notably, pharmacological suppression of TRPM8 channels and AAV-based transduction of trigeminal neurons with the Kv1.1 channel in vivo effectively reverted the nociceptive phenotype in injured animals. Altogether, our results unveil a crucial role of TRPM8 and Kv1 channels in orofacial cold allodynia, suggesting that both the specific TRPM8-blocking and the AAV-driven expression of potassium channels underlying IKD in trigeminal neurons can be effective tools to revert this damage-triggered sensory alteration.